Community Based Study about Post COVID-19 Sequelae in Salah Al-Din / Iraq - Rashad Ahmed Khaleel (Genius Journals, 2023)
Undoubtedly, the emergence of coronavirus disease 2019 (COVID-19) has led to critical devastating health effects, with a high rate of sequences and adverse effects that followed the infection for several months. Therefore, this study aims to assess the potential consequences for patients with COVID-19 infection. This community-based study was carried out on 280 participants with assured previous diagnosis of COVID-19, who attended health centers and hospitals in Salah al-Din region (Iraq) from January to April, 2023. Based on results, the main complaints of recovered patients were documented according to the following proportion: asthenia (20%), psychological (17%), respiratory (15%), neurological symptoms (13%), olfactory (10%), musculoskeletal (8%), cardiovascular and thrombotic (7%), gastrointestinal (5%) of the total study population. Most of these sequelae were observed in the period of more than 3 months of infection recovery, except for the olfactory complications, which were more in the period of less than 3 months. It was concluded that this infection has harmful sequencing effects and describes the possible prolonged complications
Keywords: COVID-19; health impacts